Type 1 diabetes mellitus in the pediatric age group: a case series - Ranabijuli, Pradeep Kumar; L. A., Nazparveen; Rajesh, T.; Patel, Nikita Nikesh (International Journal of Contemporary Pediatrics, 2025)
Diabetic ketoacidosis is the common initial presentation of type 1 diabetes mellitus in children. In a series of five cases of Type 1 diabetes mellitus who presented in the department of Pediatrics of our hospital, four children presented in the emergency department with diabetic ketoacidosis and severe dehydration. At the time of presentation, all the cases with diabetic ketoacidosis were managed according to the Milwaukee regimen as per the department protocol. None of our children developed any complications, including cerebral edema, during the treatment of diabetic ketoacidosis. The age distribution at the onset of Type 1 diabetes mellitus in our case series ranges from 1 year to 13 years. All the cases showed low c-peptide levels, high Anti- GAD antibodies and high HbA1c levels at the time of presentation. One of our cases also has celiac disease, hypothyroidism and hypercholesterolemia. One child was diagnosed to have hepatitis A infection during the hospital stay for the management of first episode of diabetic ketoacidosis, and another child developed hepatitis A infection after 2 years of diagnosis of type 1 diabetes mellitus. The child who developed hepatitis A infection later also had multiple admissions, once for non-compliance with hyperglycemia and once for an abscess with cellulitis in the neck. In one case, despite the child being clinically well and having normal growth and development, blood sugar levels are uncontrolled despite being on the maximum dose of human actrapid and glargine. Of all these cases, two are on regular insulin in the form of human Actrapid and basal insulin in the form of glargine, two are on regular insulin in the form of glulisine and basal insulin of degludec, and one is on insulin pump therapy with insulin lispro and a continuous glucose monitoring machine. All 5 children are on regular follow-up in the hospital for monitoring of growth and development, screening for complications, and optimal glycemic control.